Computational investigation of vertical upflow boiling of liquid nitrogen and effects of bubble collision dispersion force. (April 2023) - Kim, Sunjae; Lee, Jeongmin; Mudawar, Issam; Hartwig, Jason
Highlights: This study investigates vertical upflow boiling of liquid nitrogen in a circular tube. A computational model utilizing the Coupled Level Set VOF method is constructed. Predictions are compared to data from a prior benchmark investigation. Simulations are shown capable of predicting the data with high accuracy. Abstract: The present study investigates the performance of 2-D axisymmetric computational fluid dynamics (CFD) in predicting boiling characteristics of liquid nitrogen flowing vertically upwards along a uniformly heated circular tube. Investigation of the popular Volume of Fluid (VOF) model reveals (a) inaccurate surface tension calculation which degrades interface tracking, and (b) under-representation of bubble-to-bubble interaction, which stems from the innate nature of employing a single momentum equation in VOF. To alleviate VOF shortcomings, Coupled Level Set VOF (CLSVOF) is adopted in ANSYS FLUENT, including a user defined function to account for the crucial effects of bubble collision dispersion force. The CFD simulation results are validated against wall temperature and volume fraction results from prior benchmark experiments corresponding to four different wall heat flux conditions at nearly identical mass velocities. Predictions are also provided for axial variations of interfacial flow pattern, fluid temperature, and fluid velocity, flow characteristics that are very difficult to measure in cryogenic experiments. The CFD simulation results are shown to be highly accurate at predicting the nucleate boiling portion of the flow boiling curve.